Pola Komunikasi Kemitraan Program Tata Rias di Balai Besar Pelatihan Vokasi dan Produktivitas (BBPVP) Makassar - Rahmadani M , Annisa; Fikriani Amir , Izki; F. Amin , Kasma (UNIVERSITAS MUSLIM INDONESIA, 2022)
The aims of study were: (1) To find out how the communication Pattern of the Cosmetology Program Partnership in the Vocational and Productivity Training Center (BBPVP) Makassar. (2) To find out how the partnerhip pattern developed in the cosmetology program at the Vocational and Productivity Training Center (BBPVP) Makassar. The research lasted for one month and was located at the Makassar Vocational and Productivity Training Center (BBPVP) office with 6 (six) informants with different bacgrounds. This study used descriptive qualitative method. The novelty of this research is that this research is discuss the pattern of partnership communication. The results of the study indicate that the partnership communication pattern is a form of collaborative communication between agencies. The communication pattern for the cosmetology program partnership at the Makassar Vocational and Productivity Training Center (BBPVP) is running well and as expected.